1992
DOI: 10.1002/bip.360320609
|View full text |Cite
|
Sign up to set email alerts
|

Protein: Nucleic acid interactions. I. Electronic structures of cytosine, indole, and guanine complexes

Abstract: Low singlet transition energies and line strengths were calculated for the cytosine:indole:guanine complex by the INDO/1S-CI method. The chromophores were arranged in three sets of 270 intercalating geometries. Calculations were executed in the supermolecule model with single excited configurations. Errors due to basis set extension and incomplete configuration representation were assessed, for all chromophore pairs, by full BSSE correction calculations and inclusion of double-excited configurations. The inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…Valeur and Weber (1977) measured the anisotropy from immobilized tryptophan and showed that under our experimental conditions all emission occurs from the 'La transition band with limiting anisotropy, r = 0.3. We used published semiempirical calculations of indole electronic dipole transition moments to orient the two higher energy transitions, 'A -'Ba and 'A -* 'Bb, within the indole ring (Goux et al, 1976;Ilich & Prendergast, 1992). We assume that they too emit through the 'La emission dipole.…”
Section: Resultsmentioning
confidence: 99%
“…Valeur and Weber (1977) measured the anisotropy from immobilized tryptophan and showed that under our experimental conditions all emission occurs from the 'La transition band with limiting anisotropy, r = 0.3. We used published semiempirical calculations of indole electronic dipole transition moments to orient the two higher energy transitions, 'A -'Ba and 'A -* 'Bb, within the indole ring (Goux et al, 1976;Ilich & Prendergast, 1992). We assume that they too emit through the 'La emission dipole.…”
Section: Resultsmentioning
confidence: 99%